2022
DOI: 10.3390/ijerph19031900
|View full text |Cite
|
Sign up to set email alerts
|

Functional Status, Quality of Life, and Physical Activity of Senior Club Members—A Cross-Sectional Study

Abstract: This study aims to assess the functional status, quality of life, and physical activity (PA) of the elderly who are members of senior social clubs. The study included 63 participants (65–95 years old) who were members of a seniors club. The study utilized the following instruments: Barthel scale, Lawton’s scale of Instrumental Activities of Daily Living (IADL), WHO Quality of Life-BREF questionnaire, author’s survey questionnaire containing questions about the type of PA. Duration of membership in the senior c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Ensuring participants can both sustain and improve their physical activity behavior and enhance their level of social participation over time is crucial (Rogers et al, 2017; Stolarz et al, 2022). To assess the efficacy of the current physical activity intervention, the biopsychosocial model was employed (Engel, 1977; Marsac et al, 2017; Wade & Halligan, 2017).…”
Section: The Effectiveness Of Physical Activity Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ensuring participants can both sustain and improve their physical activity behavior and enhance their level of social participation over time is crucial (Rogers et al, 2017; Stolarz et al, 2022). To assess the efficacy of the current physical activity intervention, the biopsychosocial model was employed (Engel, 1977; Marsac et al, 2017; Wade & Halligan, 2017).…”
Section: The Effectiveness Of Physical Activity Interventionsmentioning
confidence: 99%
“…delivered via print-based versus web-based materials (Pischke et al, 2020). 1 The Indirect Relationship Between SPP and Social Participation Via Stage of Change to Be Physically Active Ensuring participants can both sustain and improve their physical activity behavior and enhance their level of social participation over time is crucial (Rogers et al, 2017;Stolarz et al, 2022). To assess the efficacy of the current physical activity intervention, the biopsychosocial model was employed (Engel, 1977;Marsac et al, 2017;Wade & Halligan, 2017).…”
Section: Physical Activity and Social Participationmentioning
confidence: 99%
“…Social connectedness is an important variable for older adults taking community-based group exercise 22 . Those attended senior club longer tended to have longer physical activity duration, and better quality of life 23 . However, a study has shown that social support is not significant for all adults 13 .…”
Section: Introductionmentioning
confidence: 96%
“…In relation to better functional ability, the practice of physical activity was shown to be beneficial in 63 participants aged between 65 and 95 years [ 10 ], where functional ability, in turn, was one of the factors that influence adherence to the practice of physical activity [ 11 , 12 ]. In fact, older people with a high practice of physical activity obtained better levels of functional ability and autonomy, which also increased their independence to carry out basic activities of daily life, encouraged their social ties, and improved satisfaction with their health, with the consequent socio-emotional benefits [ 13 ].…”
Section: Introductionmentioning
confidence: 99%